2018
DOI: 10.1039/c8dt01452c
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic samarium(iii) halide complexes probed by fluorescence-detected L3-edge X-ray absorption spectroscopy

Abstract: The novel series of heteroleptic Sm(iii) halide complexes provides the backdrop for a fluorescence-detected Lα1 X-ray absorption spectroscopic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 125 publications
1
27
0
Order By: Relevance
“…this has consistently been seen for {N(Si i Pr3)2} complexes and we have previously attributed this observation to the formation of carbides from incomplete combustion. 6,12,22 However, all other analytical data obtained are consistent with the bulk purity of 2-Ln and 3-Ln. h. The resultant yellow-green solid was cooled to -78 °C, dissolved in DCM (5 mL), layered with hexane (10 mL) and stored overnight at -25 °C to yield yellow-green crystals of 2-Tm (1.540 g, 46%).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…this has consistently been seen for {N(Si i Pr3)2} complexes and we have previously attributed this observation to the formation of carbides from incomplete combustion. 6,12,22 However, all other analytical data obtained are consistent with the bulk purity of 2-Ln and 3-Ln. h. The resultant yellow-green solid was cooled to -78 °C, dissolved in DCM (5 mL), layered with hexane (10 mL) and stored overnight at -25 °C to yield yellow-green crystals of 2-Tm (1.540 g, 46%).…”
Section: Discussionsupporting
confidence: 81%
“…11 In 2018, some of us showed that 1-Sm can be easily oxidized by a variety of reagents to afford heteroleptic three-coordinate Sm 3+ halide complexes [Sm{N(Si i Pr3)2}2(X)] (X = F, Cl, Br, I). 12 Herein we report the synthesis of the first structurally characterized examples of formally two-coordinate Ln 3+ [FeCp2][PF6], respectively. We have probed the electronic structures of these exotic yet structurally simple two-and three-coordinate Ln 3+ complexes by magnetic and EPR methods, supported by ab initio calculations.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous examples of analogous reactions across the f block, ,,, and these polar M–ER groups (M = Ln or An) are amenable to further derivatization . We have previously shown that although the ligand framework in [Sm­(N †† ) 2 ] is sterically demanding, the two bis­(triisopropylsilyl)­amide ligands are flexible enough to bend toward each other to accommodate further moieties at the Sm center, thus we envisaged that this redox strategy would afford a series of structurally similar complexes. ,, Gratifyingly, the separate reactions of [Sm­(N †† ) 2 ] with half an equivalent of E 2 Ph 2 in toluene gave the heteroleptic Sm­(III) complexes [Sm­(N †† ) 2 (EPh)] (E = S, 1-S ; Se, 1-Se ; Te, 1-Te ; Scheme ) in moderate to excellent yields (52–93%). Previously, Ln–EPh moieties have been investigated toward reductive elimination of E 2 Ph 2 in order to access Ln redox chemistry while avoiding the challenging synthesis of divalent precursors …”
Section: Resultsmentioning
confidence: 99%
“…Their molecular structures are confirmed by single-crystal X-ray diffraction, and electronic structures elucidated by a combination of spectroscopic and computational techniques. Exercising the methodology developed for the analogous halide series, we employ the high resolution provided by fluorescence-detected X-ray absorption spectroscopy (XAS) to experimentally calibrate our density functional theoretical (DFT) method by canvassing a range of calculation parameters. The protocol that gave the best reproduction of the Sm L 3 -edge by time-dependent (TD) DFT calculations was then applied to an examination of the one-electron oxidized and reduced variants of 2-E 2 (E = S, Se), which contain (E 2 ) −• and (E 2 ) 3–• radical ligands, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, judging whether pixels are edge points of the image through theories such as a threshold. We found that edge detection techniques can be split into two categories by reviewing the related literature, which is classic edge detection technology and deep learning-based edge detection technology [16]. On the one hand, pixel-based and sub-pixel-based edge detection technologies are included in classic edge detection technology.…”
Section: Introductionmentioning
confidence: 99%